Implementasi prinsip know your customer dalam mencegah money laundering di industri perbankan - Indrawan, Andika (Universitas Tarumanagara, 2017)
The international community considers money laundering a serious crime and follow-up crime, which must be handled more comprehensively as it relates to organized crime and terrorism. This study will explore how the bank implements the Know Your Customer instrument, related to the concern of the data protection policy & transparency policy and the effect of the implementation to prevent money laundering. The study used a normative juridical approach with an analytical description.